Projects as instruments of development administration: A qualified defence and suggestions for improvement - and Rondinelli, Dennis A. (Public Administration and Development, 1983)
Projects have become an important instrument of international assistance and of development administration because they seem to offer major advantages over other forms of planning and management. But projects have also come under increasing criticism in recent years. The benefits they offer to various interests involved in development ensure, however, that they are unlikely to be abandoned or to diminish in importance in the near future. Thus, ways must be found to make them more flexible and responsive methods of planning and managing social and human development activities. This can be done by planning, appraising and implementing projects as policy experiments, making their design and administration more learning-oriented, and using them as instruments of strategic planning and management.